Lightning risk assessment for building using intelligent smart system: article / Muhammad Izuan Omar - Omar, Muhammad Izuan (Universiti Teknologi MARA (UiTM), 2011)
Lightning is a natural hazard which occurs during thunderstorm. Direct and indirect lightning strikes can bring harm, injury or death to humans. It is important to ensure all electrical components and buildings are being protected with the suitable protection from direct and indirect lightning strikes hazards. The objective of this work is to provide a risk factor assessment calculations graphical user interface to ensure whether buildings required protections from the direct and indirect lightning strikes. The calculations of risk assessment will be based on BS6651:1999 against direct and indirect lightning strikes. The risk assessment calculated then will determine whether certain buildings need protection against direct lightning strikes or indirect lightning strikes or both. Types of protection were discussed to give an idea what type of protections can be installed to protect humans, buildings and equipment's from the hazards of direct and indirect lightning strikes.